Heyting Almost Distributive fuzzy Lattices - Berhanu Assaye Alaba; Derebew Nigussie Derso (LPPM Institut Teknologi Sepuluh Nopember, 2018)
In this paper, we introduce the concept of Heyting almost distributive fuzzy lattices (HADFL) using the concepts of Heyting almost distributive lattices (HADL), almost distributive fuzzy lattices, fuzzy partial order relation and fuzzy Heyting algebra. Using the properties of fuzzy Heyting algebra, we also give a necessary and sufficient condition for an HADFL to be fuzzy Heyting algebra (FHA).